Correlation between Age, Working Period and Working Posture with Musculoskeletal Complaints in Oil Palm Plantation Factory Workers at PT. X - Prayogi Joko Pamungkas; Rd. Halim (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study was to determine the relationship between age, work period, and work posture with musculoskeletal complaints. This type of research is quantitative observational with a cross-sectional method, the study population is all workers in the production division of the oil palm plantations of PT. X totaled 35 workers, sampling was carried out using the total sample technique. Data collection methods used interviews and observation with the RULA (Rapid Upper Limb Assessment) instrument for assessing work posture and the Nordic Body Map questionnaire to assess the level of musculoskeletal complaints. Data analysis with chi-square test. The results showed that the proportion of Musculoskeletal Disorders Complaints (MSDs) showed there was a significant relationship between the age variable p-value: 0.000, work posture variable: 0.007 with musculoskeletal complaints while there was no significant relationship between years of service p-value: 0.176 and musculoskeletal complaints. There is a relationship between age and work posture with MSDs complaints. The need for education with good work posture in preventing MSDs complaint control